The convergence of digitalization and internationalization: a literature review and future research agenda / Richard Seow Yeaw Chong - Seow, Richard Chong Yeaw (Universiti Teknologi MARA, Selangor, 2022)
The interplay phenomenon of digitalization and internationalization (IDI) is gaining scholarly traction in the recent two decades when digitalization acts as an effective fuel for internationalization and internationalization activities reciprocally cry out for a greater digitalization revolution. Digital companies (DCs), born-digital companies (BDCs), and born-global companies (BGCs) are the new entrants to the literature. Despite burgeoning scholarly interest in this research domain, it is a relatively young research domain with limited scholarly literature. This paper aims to provide a clear picture of this interplay phenomenon and offers useful insights for future research to further enrich the extant literature on digitalization and internationalization. What do we know about the interplay phenomenon of digitalization and internationalization and what else should we investigate further in this domain? This paper reveals that despite the recent mushrooming literature on both digitalization and internationalization themes, there lie great research opportunities in topics related to IDI, and international business theories (IBT) for both large and small multinational enterprises (MNEs) as well as risks associated with digitalization and internationalization. The study contributes to the literature by discussing the gaps in the literature and offering academicians and researchers new research venues to enrich the extant literature in this domain.